2009
DOI: 10.1002/cncr.24383
|View full text |Cite
|
Sign up to set email alerts
|

Cancer mortality in patients with schizophrenia

Abstract: BACKGROUND: Schizophrenia has been associated with a rate of premature mortality that is 2 to 3 times higher than that in the general population. Although the role of cancer in this excess mortality remains unclear, previous incidence or mortality studies found contradictory results. METHODS: In 1993, a large prospective study was initiated in a cohort of 3470 patients with schizophrenia to examine cancer‐related mortality and predictors. Standardized mortality ratios (SMRs) were calculated, adjusting for age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(72 citation statements)
references
References 29 publications
3
67
1
1
Order By: Relevance
“…In another study based on the linked data from death certificates and the mental health system in Ohio, Musuuza et al (14) reported higher standardized mortality rates (SMRs) of lung cancer among people with mental illness than the general population, with SMRs ranging from 3 to 5 times higher stratified by race and gender, respectively (14). With respect to specific mental health disorders, a French study observed a more than 2-fold increase in the mortality of lung cancer among men with schizophrenia compared to the general population (13). Two other cohort studies identified psychological stress (12) and schizophrenia (21) as significant may exist for the observed associations in these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study based on the linked data from death certificates and the mental health system in Ohio, Musuuza et al (14) reported higher standardized mortality rates (SMRs) of lung cancer among people with mental illness than the general population, with SMRs ranging from 3 to 5 times higher stratified by race and gender, respectively (14). With respect to specific mental health disorders, a French study observed a more than 2-fold increase in the mortality of lung cancer among men with schizophrenia compared to the general population (13). Two other cohort studies identified psychological stress (12) and schizophrenia (21) as significant may exist for the observed associations in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Non-small cell lung cancer (NSCLC) comprises 85% to 90% of all lung cancers (30). Previous studies have found increased mortality among lung cancer patients with mental illness (1, 10, 11, 13, 14, 31, 32). However, it is not clear what factors may contribute to the increased mortality while it can be reasonably postulated that treatment and treatment adherence may differ between patients with and without a mental health disorder.…”
Section: Introductionmentioning
confidence: 92%
“…In particular, and perhaps surprisingly, deaths due to cancer and alcohol were lower in the SMI group compared to the Glasgow group. To date, the literature surrounding cancer deaths in individuals with SMI has been mixed, with some studies reporting elevated rates [31], while others report lower rates of cancer deaths [32]. A recent meta-analysis of incidence of cancer [33], reported that pooled overall rates of cancer incidence were not significantly increased in individuals with schizophrenia compared to controls (Standardised Incidence Rate (SIR) 1.05, 95% CI 0.95-1.15) and although incidence of lung cancer was increased, when adjusted for smoking there was no difference in incidence rates.…”
Section: Discussionmentioning
confidence: 99%
“…Death from unnatural causes appears to be 10–20 times higher in schizophrenia than in the general population (2, 4, 13). Suicide and accidents accounted for about 40% of the extra deaths, while 60% were from natural causes (4, 8, 14, 15). …”
Section: General Mortality In Schizophreniamentioning
confidence: 99%